2019
DOI: 10.1096/fj.201802614rrr
|View full text |Cite
|
Sign up to set email alerts
|

Erianin alleviates diabetic retinopathy by reducing retinal inflammation initiated by microglial cells via inhibiting hyperglycemia‐mediated ERK1/2–NF‐κB signaling pathway

Abstract: Blood‐retinal barrier (BRB) breakdown is a typical event in the early stage of diabetic retinopathy (DR). This study aims to elucidate the protection of erianin, a natural compound isolated from Dendrobium chrysotoxum Lindl, against DR development. Erianin alleviated BRB breakdown and rescued the reduced claudin1 and occludin expression in retinas from streptozotocin‐induced diabetic mice. Erianin reduced microglial activation, ERK1/2 phosphorylation, NF‐κB transcriptional activation, and the elevated TNF‐α ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…Erianin has been studied mainly for its antiangiogenic properties. In preclinical studies, 100 mg/kg per day of erianin induced growth delay in tumors [199]. In 2015, erianin was first introduced as a DR therapy option, by inhibiting the NF-κβ signaling pathway, thus inhibiting retinal…”
Section: Polyphenols: Anthocyanins and Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Erianin has been studied mainly for its antiangiogenic properties. In preclinical studies, 100 mg/kg per day of erianin induced growth delay in tumors [199]. In 2015, erianin was first introduced as a DR therapy option, by inhibiting the NF-κβ signaling pathway, thus inhibiting retinal…”
Section: Polyphenols: Anthocyanins and Resveratrolmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity inflammation in preclinical studies [198,199]. Nevertheless, clinical studies are still needed to assess its clinical relevance in DR and its potential use as a concomitant therapy in this disease.…”
mentioning
confidence: 99%
“…been demonstrated to alleviate diabetic retinopathy by reducing retinal inflammation inhibited by microglia cells via inhibiting hyperglycemia-mediated ERK1/2-NF-κB signal pathway. 13 Erianin also showed a protective effect against high glucose-induced oxidative injury in renal tubular epithelial cells. 14 Although the pharmacological effects have been investigated extensively, the pharmacokinetics and metabolism of erianin have been studied insufficiently.…”
mentioning
confidence: 95%
“…Therefore, erianin has the potential to be developed as an anticancer drug. Besides its antitumor activity, erianin has been demonstrated to alleviate diabetic retinopathy by reducing retinal inflammation inhibited by microglia cells via inhibiting hyperglycemia‐mediated ERK1/2‐NF‐κB signal pathway . Erianin also showed a protective effect against high glucose‐induced oxidative injury in renal tubular epithelial cells …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that erianin has antiangiogenic and antitumor activities (Gong, Fan, Liu, et al, 2004; Gong, Fan, Wu, Hu, & Wang, 2004; Sun et al, 2016; Li, Wang, & Liu, 2001; Wang et al, 2016). The antitumor mechanism mainly involves inducing cancer cell apoptosis and modulating the ROS/JNK signaling pathways (Zhang, Ouyang, et al, 2019; Zhu et al, 2019). In addition, erianin has been demonstrated to alleviate diabetic retinopathy by reducing retinal inflammation inhibited by microglia cells via inhibiting the hyperglycemia‐mediated ERK1/2‐NF‐ κ B signal pathway (Zhang, Zhang, Wei, & Liu, 2019).…”
Section: Introductionmentioning
confidence: 99%